SCHWANNOMA OF THE HEAD AND NECK REGION: A CASE SERIES IN A TERTIARY HEALTH CENTRE IN WESTERN ODISHA - KUMARI, PRIYA; PANDA, PREMANAND; PANIGRAHI, RUDRA; MISHRA, PRAGNYA P. (International Journal of Current Pharmaceutical Research, 2024)
Objective: Schwannoma is a benign peripheral nerve sheath tumour. Previously referred to as Neurilemmomas. It is a slow-growing tumour. The commonest site is the limb with a predilection to the upper limb. But, it has a 25–48% predilection for nerves of the head and neck. In the oral cavity, the commonest site is said to be the tongue. Methods: We report three cases of histopathologically diagnosed Schwannoma at unusual sites. The first case was a 52 y old lady with a palpable, firm, painless swelling in the occipital region of the scalp of size 2.0 x 1.0 x 1.0 cm. The second case was a 29 y old woman with a painless scalp swelling of 1 cm by 1 cm. The third case was a 23 y old boy who presented with a slow-growing and painless pedunculated swelling in the posterior pharyngeal wall for a year. All cases showed classical histopathologic pictures on microscopy. Results: All the patients were evaluated pre-operatively and subjected to an excisional biopsy. The post-operative period was uneventful and everything went according to plan for a full year. Conclusion: Schwannomas exhibit a slow growth rate, are present in all age groups, and are not specific to one gender. Extremities are the most common locations to occur, but some rare sites like the scalp, oral cavity, retroperitoneum, and internal viscera also exist. Magnetic resonance imaging (MRI) is helpful in those lesions, providing useful information about the location and nature of the lesion, eliminating differential diagnosis, and thus providing correct management plans.